2021
DOI: 10.1186/s12957-021-02403-2
|View full text |Cite
|
Sign up to set email alerts
|

Imaging surveillance for the detection of ipsilateral local tumor recurrence in patients who underwent oncoplastic breast-conserving surgery with acellular dermal matrix: abbreviated MRI versus conventional mammography and ultrasonography

Abstract: Background To evaluate the usefulness of surveillance-abbreviated magnetic resonance imaging (AB-MRI) for the detection of ipsilateral local tumor recurrence (LTR) in patients who underwent oncoplastic breast-conserving surgery (BCS) with acellular dermal matrix (ADM) by comparing its diagnostic performance with that of mammography (MG) and ultrasonography (US). Methods The postoperative MG, US, and AB-MRI findings of the ipsilateral breast and pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 53 publications
0
8
0
Order By: Relevance
“…The literature describes a spectrum of imaging findings for ADM on various modalities. AlloDerm appears as an equal to high density mass on mammography without obscuration of calcifications [7,8,10]. On ultrasound, AlloDerm has been described as isoechoic to hypoechoic masses with smooth margins and variable internal color flow [8,10,11].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The literature describes a spectrum of imaging findings for ADM on various modalities. AlloDerm appears as an equal to high density mass on mammography without obscuration of calcifications [7,8,10]. On ultrasound, AlloDerm has been described as isoechoic to hypoechoic masses with smooth margins and variable internal color flow [8,10,11].…”
Section: Discussionmentioning
confidence: 99%
“…AlloDerm appears as an equal to high density mass on mammography without obscuration of calcifications [7,8,10]. On ultrasound, AlloDerm has been described as isoechoic to hypoechoic masses with smooth margins and variable internal color flow [8,10,11]. On MRI, AlloDerm was isointense to glandular tissue on non-contrast fat-saturated T1-weighted images, hyperintense on fat-saturated T2-weighted images, and had variable post-contrast enhancement [7,8,10,12].…”
Section: Discussionmentioning
confidence: 99%
“…They may appear as iso-to-hypoechoic masses with a folded, sheet-like structure with posterior acoustic shadowing, and with or without color flow [7 , 8] . On MRI, an ADM shows iso-signal intensity to glandular tissue in a non fat-satured T1-weighted image, and low signal intensity in a fat-saturated T2-weighted image with none to mild dynamic contrast enhancement [4 , 8 , 9] .…”
Section: Discussionmentioning
confidence: 99%
“…Lee et al 2 describes 3 cases where ADM seemed as circumscribed masses isodense to glandular tissue without obscuring calcifications, similar to findings of Tran et al, 3 although these studies used ADM as a hammock/sling or to fill lumpectomy defects, not in neonipple reconstruction. To increase detection of local tumor recurrence, Young Kim et al 15 suggested using the surveillance-abbreviated magnetic resonance imaging for patients who underwent breast-conserving therapy with ADM, which demonstrated a high sensitivity in detecting ipsilateral local tumor recurrence without delayed diagnosis as a result of postoperative changes with ADM filler.…”
Section: Discussionmentioning
confidence: 99%